If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 + -3x = x + 23 Reorder the terms: 27 + -3x = 23 + x Solving 27 + -3x = 23 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 27 + -3x + -1x = 23 + x + -1x Combine like terms: -3x + -1x = -4x 27 + -4x = 23 + x + -1x Combine like terms: x + -1x = 0 27 + -4x = 23 + 0 27 + -4x = 23 Add '-27' to each side of the equation. 27 + -27 + -4x = 23 + -27 Combine like terms: 27 + -27 = 0 0 + -4x = 23 + -27 -4x = 23 + -27 Combine like terms: 23 + -27 = -4 -4x = -4 Divide each side by '-4'. x = 1 Simplifying x = 1
| 26x+5=5(5x+3) | | 13+8x=3x+13 | | 3(y+9)=4y+27 | | 40x+8y+30z= | | y^3-19y^2+90y=0 | | y+3=-7(x-6) | | 4(p+3)=2(2p+8)-4 | | y^3-19y^2+90=0 | | 4(x+5)+3=4x+4 | | 6(p+2)=3(2p+5)-3 | | (t-4)2+6=0 | | 8x-7-4x=x+3+x | | t-3=19 | | 9(x+5)+2=9x+7 | | -(8p+1)-(-7p-6)=-1 | | 25x^2+25x+4=0 | | .2f-5=1 | | X^2-11x=-30 | | .25f-5=1 | | 5x^2+18x+16=0 | | 8x-8-5x=x+9+x | | -8x=15+5y | | 6+5x-(-3x)= | | 7(x+3)+3=-11 | | 7(x+3)+3=7x+24 | | -3(2y-2)-y=-3(y-4) | | 3x^2+27x+8=0 | | 25x^2+55x+28=0 | | 5x+19=2(2x+5) | | (y-3)-(y+6)=5y | | 4x-3=9+2x | | 3x+5(3x-4)=2-4x |